Applying Radio Frequency Identification to Optimize Goods Issue and Goods Receipt Procedures for Raw Material at Song Thu Corporation - Pham, Dac Khoa (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - Logistics and Digital Supply Chain Management; 2021-2025.